2017
DOI: 10.1111/1556-4029.13563
|View full text |Cite
|
Sign up to set email alerts
|

Using Alkylate Components for Classifying Gasoline in Fire Debris Samples

Abstract: The characteristic that discriminates gasoline from other ignitable liquids is that it contains high-octane blending components. This study elaborates on the idea that the presence of gasoline in fire debris samples should be based on the detection of known high-octane blending components. The potential of the high-octane blending component alkylate as a characteristic feature for gasoline detection and identification in fire debris samples is explored. We have devised characteristic features for the detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Generation of gasoline data for the simulations. Details of collecting gasoline reference samples are provided by Peschier et al 27 . The gasoline samples were collected in the period of May-August 2011 from 230 different petrol stations in the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
“…Generation of gasoline data for the simulations. Details of collecting gasoline reference samples are provided by Peschier et al 27 . The gasoline samples were collected in the period of May-August 2011 from 230 different petrol stations in the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
“…In this study within-class differences were observed for all three IL types but differences were most pronounced for gasoline. Various approaches to distinguish gasoline samples are described in literature, such as (i) substituted naphthalenes [7,32]; (ii) alkylate compounds [9]; and (iii) octane rating [33]. Figure 6 shows an example of two different gasoline batches and the variation observed.…”
Section: Characterization Of Ilsmentioning
confidence: 99%
“…Fire debris analysis is a complex and challenging task due to several interfering factors, such as (i) substrate variability and released pyrolysis products that are also commonly found in ignitable liquids (IL); (ii) the complex chemical composition of different types of ignitable liquid; (iii) evaporation and consumption of the ignitable liquid during a fire; and (iv) (bio)-degradation of fire debris samples. Several studies have been conducted based on classification and within-class differentiation with the use of neat ignitable liquids in order to improve the detection and classification of ILRs in fire debris samples [6][7][8][9]. An overview of challenges in terms of the variety of ignitable liquids, classification and matrix interferences in fire debris analysis has been provided by Baerncopf et al [10].…”
Section: Introductionmentioning
confidence: 99%